Emotional intelligence training for sports coaches - evaluation of a time-effective online intervention and its effects on coaching efficacy - Zajonz, P.; Lautenbach, F.; Laborde, S. (Journal of Applied Psychology, 2024)
Emotional Intelligence (EI) describes the way an individual manages one`s own and others` emotions. In the context of sports, higher EI has been associated with more successful performance and coping. Past studies with athletes have shown that EI can be improved through training. However, the present study is the first evaluating an EI training specifically designed for sport coaches. Therefore, 57 coaches from individual sports (e.g., running, swimming, triathlon; recreational to international level) were randomized into intervention group (EI training) and control group (health and well-being train ing). Both trainings consisted of five weeks (15 sessions of 10-15 minutes), and in response to coaches` needs for accessible and time effective training tools they were carried out online. Coaches` EI and beliefs in their coaching skills (i.e., coaching efficacy) were assessed before and after the training. We found that coaches` inter personal emotional competencies, game strategy efficacy, and team efficacy improved in the intervention group, but not in the control group. In addition, results replicated a positive correlation between EI and coaching efficacy. The present study contributes to EI research and coaching science, especially by addressing the call for empiric ally evaluated coaching education. Overall, we can recommend the implementation of an EI training for coaches in applied sport psy chological work and for coaching education programs.